Implementasi Prinsip-Prinsip Good Corporate Governance Pada Lembaga Perkreditan Desa (LPD) Desa Adat Peguyangan - Santiari, Ni Made Rai; Hutnaleontina, Putu Nuniek; Yuliantari, Ni Putu Yeni (UNHI Press, 2025)
LPD is a financial institution that plays an important role in the Pakraman village community in Bali. LPDs have a positive impact on the economy, but in reality there are often problems regarding LPD performance which actually harm customers. The Peguyangan Traditional Village LPD has good performance achievements, which cannot be separated from the implementation of good corporate governance in all its business activities. The aim of this research is to determine and analyze the implementation of good corporate governance principles in the Peguyangan Traditional Village LPD. Based on the problems studied, this research uses qualitative methods, with data from interviews and documentation in the field. Based on data collected from interviews with the Head of the LPD, it is stated that the principle of transparency is applied by providing information regarding the development of the Peguyangan Traditional Village LPD, not only known to the internal LPD but also the general public, especially the manners of the Peguyangan Traditional Village, the principle of accountability is applied by encouraging every employee to work. responsible for each task, the principle of responsibility is carried out by having a social service program based on Tri Hita Karana for the community, the principle of independence is carried out by making their own considerations in determining the interest rate on each financial product, decision making and every village manner is given the opportunity to provide input, the principle of equality This is done to provide the opportunity to convey input ideas and suggestions to the LPD from employees through communication forums every week, and the community through its representatives (prajuru banjar) at meetings (paruman adat village) which are held three times a year.